Validitas dan Reliabilitas Indeks Kebutuhan Perawatan Ortodonti Interseptif oleh Orang Tua (IKPOI-OT) - Amanda, Felicia; Yusra, Yohana (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Malocclusion is a common dental and oral health problem that occurs children in mixed dentition. Interceptive orthodontics is an orthodontics treatment in children Early detection is necessary for interceptive orthodontic treatment. One of the ways for early detection by using index. Indeks Kebutuhan Perawatan Ortodonti Interseptif oleh Orang Tua (IKPOI-OT) is an index used to measure the need of interceptive orthodontic treatment that can be used by their parents. Objectives: To determine the validity and reliability of Indeks Kebutuhan Perawatan Ortodonti Interseptif oleh Orang Tua (IKPOI-OT) in children aged 8-11 years (mixed dentition period). Methods: This study is an analytical observational study with cross-sectional design with a sample of 34 people. The data were processed using Pearson’s Product Moment for validity test and Guttman Split-Half Coefficient for reliability test. Results: Based on data analysis results, there are 9 questions that shows valid and reliable with the highest correlation value 0,879 and the lowest 0,528 while for the Guttman Split-Half Coefficient value 0,839. Conclusion: Indeks Kebutuhan Perawatan Ortodonti Interseptif oleh Orang Tua (IKPOI-OT) is a valid and reliable index that can be used to measure interceptive orthodontic needs for children in mixed dentition.